Diagnostic and Therapeutic Potential of Extracellular Vesicles in B-Cell Malignancies - Gargiulo, Ernesto; Morande, Pablo Elías; Largeot, Anne; Moussay, Etienne; Paggetti, Jérôme (Frontiers in Oncology, 2020)
Extracellular vesicles (EV), comprising microvesicles and exosomes, are particles released by every cell of the organism, found in all biological fluids and commonly involved in cell-to-cell communication through the transfer of cargo material such as miRNA, proteins, and immune-related ligands (e.g. FasL and PD-L1). An important characteristic of EV is that their composition, abundance and roles are tightly related to the parental cells. This translates into a higher release of characteristic pro-tumor EV by cancer cells that leads to harming signals towards healthy microenvironment cells. In line with this, the key role of tumor-derived EV in cancer progression was demonstrated in multiple studies and is considered a hot topic in the field of oncology. Given their characteristics, tumor-derived EV carry important information concerning the state of the tumor cells. This can be used to follow the outset, development and progression of the neoplasia and to evaluate the design of appropriate therapeutic strategies. In keeping with this, the present brief review will focus on B-cell malignancies and how EV can be used as potential biomarkers to follow disease progression and stage. Furthermore, we will explore several proposed strategies aiming at using biologically engineered EV for treatment (e.g. drug delivery mechanisms) as well as for impairing biogenesis, release and internalization of cancer-derived EV with the final objective to disrupt tumor-microenvironment communication.